In vitro CLONAL PROPAGATION OF PINEAPPLE (Ananas comosus L. Merr) VARIETIES CHAMPAKA AND HAWAIIAN - Saucedo Aguiar, Silvia Gicela (2008)
This work was realized by the purpose of establishing a protocol for the spread in vitro of pineapple (Ananas comosus (L) Merr), as well as to determine the best concentrations of regulators of growth in the establishment, multiplication, to take root and acclimatization ex vitro. For the establishment of pineapple var. Champaka and Hawaiian the best concentration was in a way of culture shaped by the totality of you them go out of the MS suplement with BAP (0.5 mg L-1); AIB (1.0 mg L-1) and ANA (1.0 mg L-1) 47 and 56 % of survival being obtained respectively. For the proliferation of outbreaks the best concentration was in a way of culture shaped by the totality of you them go out of the MS suplement with 3.5 and 4.0 mg L-1 of BAP in the var. Champaka and the hawaiian var. with 3.5 mg L-1 of BAP. For the enraizamiento ex vitro and aclimatization the best response to the number of roots appeared in the witness (without hormone) var. Hawaiian with an average of 7.25. The major length was demonstrated in the witness (without hormone) by 3.55 cm. There was obtained a survival of 93.75 % for the Hawaiian var. and 79.16 % for the var. champaka. The best results in the enraizamiento and acclimatizations ex vitro of vitroplantas of pineapple(pine cone) were obtained by the witness in the variety Champaka and by the auxina ANA (acid naptalenacetico) 50 mg L-1 in the Hawaiian var.